2022
DOI: 10.3390/cancers14102491
|View full text |Cite
|
Sign up to set email alerts
|

Antagonizing Glutamine Bioavailability Promotes Radiation Sensitivity in Prostate Cancer

Abstract: Nearly half of localized prostate cancer (PCa) patients given radiation therapy develop recurrence. Here, we identified glutamine as a key player in mediating the radio-sensitivity of PCa. Glutamine transporters and glutaminase are upregulated by radiation therapy of PCa cells, but respective inhibitors were ineffective in radio-sensitization. However, targeting glutamine bioavailability by L-asparaginase (L-ASP) led to a significant reduction in clonogenicity when combined with irradiation. L-ASP reduced extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…L-asparaginase (L-ASP) reduced extracellular asparagine and glutamine, but the sensitization effects were driven through glutamine depletion. L-ASP resulted in G2/M checkpoint blockade [40]. In addition, blocking anaplerotic entry of glutamine into the TCA cycle enhanced the sensitivity of K-Ras mutant cancer cells to cytotoxic drugs [41].…”
Section: Discussionmentioning
confidence: 99%
“…L-asparaginase (L-ASP) reduced extracellular asparagine and glutamine, but the sensitization effects were driven through glutamine depletion. L-ASP resulted in G2/M checkpoint blockade [40]. In addition, blocking anaplerotic entry of glutamine into the TCA cycle enhanced the sensitivity of K-Ras mutant cancer cells to cytotoxic drugs [41].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has found that PCa cells show increased Gln metabolism, indicating that Gln metabolism plays a significant driving role in the initiation and progression of PCa. 81 In PCa cells, the synthesis pathway of Gln is activated, and the level of Gln transporter protein is also increased. Studies have shown that the abnormal expression of the transcription factor c-Myc is associated with the activation of the Gln synthesis pathway in PCa cells.…”
Section: Amino Acid Metabolism and Pcamentioning
confidence: 99%
“…Recent studies reveal that many types of tumor growth are highly dependent on glutamine, including non-small cell lung cancer, breast cancer and glioblastoma [ 4 ]. Likewise, glutamine is also one of the key nutrients that drive PCa progression; patients with higher glutamine levels often have poorer prognoses [ 5 ]. A recent study reported that the survival of radiation resistant PCa cells and stem cells relies on a large amount of glutamine, and that the cells undergo growth inhibition after glutamine deprivation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%